Establishment and Validation of a Two-Step LAMP Assay for Detection of Bacillus cereus-Group Isolates in Food and Their Possibility of Non-haemolytic Enterotoxin Production - Annemarie Busch; Ulrich Schotte; Nadja Jeßberger; Hendrik Frentzel; Madeleine Plötz; Amir Abdulmawjood (Frontiers in Microbiology, 2022)
The closely related members of the Bacillus cereus-group can mainly only be differentiated by whole genome sequencing. Among them, there are potentially toxin-producing bacteria. When consumed with food, these can cause vomiting or diarrhea and abdominal cramps. To date, although no EU-wide threshold exists, a bacterial count of 105 CFU/g can be regarded as critical. Specific and rapid detection of the bacteria is difficult due to their close relationship, and no loop-mediated isothermal amplification (LAMP) assay has been developed so far to detect potentially toxin-producing members of the B. cereus-group. Aim of this study was to develop a LAMP method to detect critical cell counts specifically and rapidly of potentially non-haemolytic enterotoxin (NHE)-producing cells of this group. A two-step LAMP assay was developed. First, the target sequence groEL was used to determine the representatives of the B. cereus-group. Second, since bacteria in which nheB is present are basically capable of producing enterotoxins, this gene was chosen for detection. The specificity of the developed assay was 100% for B. cereus-group isolates and 93.7% for the detection of nheB. The analytical sensitivity was 0.1 pg DNA/μl. Using simplified DNA extraction by boiling, cell-based sensitivity was determined. Targeting groEL and nheB, 11.35–27.05 CFU/reaction and 11.35–270.5 CFU/reaction were detectable, respectively. Artificially contaminated samples were investigated to prove the application in foods. Direct detection of the critical value of B. cereus-group cells was possible in 83.3% of samples and detecting the toxin-gene 50% thereof. After a 6-h incubation period, the detection rate increased to 100 and 91.7%, respectively. Additionally, 100 natively contaminated food samples were tested, also quantitatively and culturally. Samples with relevant contamination levels were reliably detected using groEL-LAMP. After a 6-h incubation period, isolates bearing the toxin gene nheB could also be reliably detected. In addition, colony material was boiled and used as a LAMP template for simple detection. Specificity for the B. cereus-group was 100 and 93.22% detecting nheB. The study demonstrated that screening of food samples with the groEL/nheB-LAMP assay can be performed within 1 day, making it possible to detect critical levels of potentially NHE-toxin-producing cells of the B. cereus-group.